Two Phase Dual-Stator Axial-Flux PM BLDC Motor With Ironless Rotor Using Only-Pull Drive Technique - Tanveer Yazdan; Shahid Atiq; Byung-Il Kwon; Noman Baloch; Jung-Woo Kwon (IEEE Access)
This paper proposes a two-phase dual-stator axial-flux permanent magnet brushless dc motor with an ironless rotor for higher torque per magnet volume using the only-pull drive technique. The advantage of the ironless rotor is that it reduces magnet volume by providing an effective flux linkage, while the only-pull drive technique, which involves only the pull process, benefits from the use of thin magnets that do not experience the irreversible demagnetization. The axial-flux configuration of the proposed dual-stator motor was adopted because of its capability of achieving the desired trapezoidal back electromotive force that maximizes the advantages of the only-pull drive technique. The thin magnets were fixed on the ironless rotor using a non-magnetic structure, and the stator was particularly designed to implement the only-pull drive technique. The performance of the motor was analyzed in terms of torque per magnet volume using the finite element analysis and validated by the experimental results.